The influence of reflective inquiry on professional development of student teachers / Mohd Syazwan Wan Mahzan - Wan Mahzan, Mohd Syazwan (2013)
Providing opportunities for student teachers “to reflect on, and benefit from real classroom experience" during the reflective inquiry sessions is necessary to empower student teacher learning via teaching (Heng and Khim, 2004, p. 33). The present study was aimed at identifying what was the focus of reflections centralized by the practicum supervisors during the implementation of the reflective inquiry sessions. The researcher also wished to examine the student teachers' levels of reflectivity experienced by the student teachers during the reflective sessions and to investigate to what extent the professional dialogue sessions have inculcated the student teachers’ self-efficacy beliefs in realizing their strengths and weaknesses in teaching. Five student teachers from Institut Pendidikan Guru Malaysia Kampus Kota Bharu, Kelantan who were undergoing practicum in secondary schools around Kota Bharu were selected as the research participants. Qualitative interviewing based on the general interview guide and semistructured interview approach was employed as a method to collect the required data from the sample. From the results of the study, six foci of reflections were prominent in the discussions between the research participants and their respective supervisors during the reflective inquiry sessions. Reflecting on the research participants' levels of reflectivity, the analysed data showed that 45% of the interview entries were coded at level one which is Technical Rationality (TR), 50% at level two of reflectivity, Practical Action (PA), and only 4 interview entries which cover 5 % out of the total entries indicated reflection at level three, Critical Reflection (CR). The findings also found out that the development of the research participants' self-efficacy beliefs in realizing their strengths and weaknesses in teaching was due to three contributing factors: the employment of reflective techniques by the supervisors, the value of accepting the strengths and weaknesses in teaching experienced by the research participants and the applications of the outcomes that were gained during the reflective inquiry sessions on the upcoming lessons. The issue of lack of time allocated to conduct the reflective inquiry sessions was underscored as key reason for the lack of success to professionalize teaching for learning in reflective inquiry.